Cultural factors and implementation of ergonomics in developing countries : (an industrial psychological study of selected cultural factors with specific reference to the transfer of technology within the eastern Mpumalanga Province, one of nine provinces of South Africa) - Strydom, J. (Joyce) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm)--Stellenbosch University, 2000.